Characterization of Anderson promoters and construction of chemostat systems for study of quorum sensing - Yin, Yuan (2015)
Synthetic biology engineers genetic sequences to reprogram organisms. To construct and to model genetic devices that coordinate desirable biological reactions, the performance of each genetic part needs to be quantitatively understood. Due to the complexity of biological systems, behavior of parts differ when incorporated in different biological devices and when characterization environment alters. In the first part of the project, 4 Anderson promoters (BBa_J23101, J23102, J23108 and J23116) covering a range of promoter strength were characterized in 2 plasmid backbones (SVc and pBbE8k) with E. coli MG1655 as chassis. As more complex genetic devices being conceived, single microorganism system falls short to perform all the functions as desired. Microbial consortia where multiple populations of microorganism cooperates are frequently adopted as an alternative. Effective cooperation of microbial consortia require robust intercellular communication. The second and third part of the project encompass construction of macroscopic and PDMS-based microfluidic chemostat for studying quorum sensing-based intercellular communication between engineered microbes. It was demonstrated in this FYP that: 1. promoter strength varies in different backbones; 2. our macroscopic chemostat could effectively prolong exponential growth of bacteria; 3. sensitivity of biosensor for signaling molecule (AHL) is higher in chemostat than that in batch culture; 4. AHL production of engineered cell falls short compared to that of natural AHL producer Pseudomonas aeruginosa LN7; 5. the design of microfluidic chemostat has satisfactory performance in transferring AHL between chambers.